Modular Ontologies for Genetically Modified People and their Bioethical Implications - So, Derek; Sladek, Robert; Joly, Yann (Nanoethics, 2024)
Participants in the long-running bioethical debate over human germline genetic modification (HGGM) tend to imagine future people abstractly and on the basis of conventionalized characteristics familiar from science fiction, such as intelligence, disease resistance and height. In order to distinguish these from scientifically meaningful terms like “phenotype” and “trait,” this article proposes the term “persemes” to describe the units of difference for hypothetical people. In the HGGM debate, persemes are frequently conceptualized as similar, modular entities, like building blocks to be assembled into genetically modified people. They are discussed as though they each would be chosen individually without affecting other persemes and as though they existed as components within future people rather than being imposed through social context. This modular conceptual framework appears to influence bioethical approaches to HGGM by reinforcing the idea of human capacities as natural primary goods subject to distributive justice and supporting the use of objective list theories of well-being. As a result, assumptions of modularity may limit the ability of stakeholders with other perspectives to present them in the HGGM debate. This article examines the historical trends behind the modular framework for genetically modified people, its likely psychological basis, and its philosophical ramifications.